Polymorphism of the 5-HT transporter and response to antidepressants: randomised controlled trial. - Lewis, G; Mulligan, J; Wiles, N; Cowen, P; Craddock, N; Ikeda, M; Grozeva, D; Mason, V; Nutt, D; Sharp, D; Tallon, D; Thomas, L; et al. (2011)
BACKGROUND: Antidepressants exhibit a variety of pharmacological actions including inhibition of the serotonin and noradrenaline transporters. We wished to investigate whether genetic variation could be used to target or personalise treatment, in a comparison of selective serotonin reuptake inhibitors (SSRIs) with noradrenaline reuptake inhibitors (NARIs). AIMS: To test the hypothesis that patients homozygous for the long (insertion) polymorphism of the serotonin transporter (5-HTTLPR) have an increased response to SSRI antidepressants but not to NARI antidepressants. METHOD: In an individually randomised, parallel-group controlled trial, people meeting criteria for a depressive episode who were referred by their general practitioner were randomised to receive either citalopram (an SSRI) or reboxetine (an NARI). Randomisation was by means of a remote automated system accessed by telephone. The main outcome was depressive symptoms, measured by Beck Depression Inventory (BDI) total score 6 weeks after randomisation. The trial was registered with the International Standard Randomised Controlled Trials Number registry (ISRCTN31345163). RESULTS: Altogether 298 participants were randomised to receive citalopram and 303 were randomised to reboxetine. At 6 weeks follow-up, complete data were available for 258 participants taking citalopram and 262 taking reboxetine. We found no evidence to support an influence of 5-HTTLPR on outcome following antidepressant treatment. The interaction term for BDI score at 6 weeks was 0.50 (95% CI -2.04 to 3.03, P = 0.70), which indicated that responses to the SSRI and NARI were similar irrespective of 5-HTTLPR genotype. CONCLUSIONS: It is unlikely that the 5-HTTLPR polymorphism alone will be clinically useful in predicting response to antidepressants in people with depression.